Notes on the genus Amorphophallus Blume ex Decne. (Araceae) of northwestern Luzon, Philippines, including a new species. Issue 6 (13th March 2022) - Calaramo, Michael A.; Batuyong, Mae Ann R.; Bulawin, Norilyn F.; Alejandro, Grecebio Jonathan D.
Abstract : A botanical exploration conducted by the Northwestern University – Biodiversity Research Unit and other collaborating institutions in the Ilocos Region, Northwestern Luzon, Philippines, led to the documentation of five Amorphophallus species in the area. Here, we provide new distributional records for A. longispathaceus and A. urceolatus, an expanded description and new conservation status for A. adamsensis, and describe new color forms of A. paeoniifolius . Moreover, the new species Amorphophallus flammeus is described and compared to its closest relatives.